Three novel transition metal complexes of 6-methyl-2-oxo-quinoline-3-carbaldehyde thiosemicarbazone: synthesis, crystal structure, cytotoxicity, and mechanism of action. Issue 29 (24th March 2017) - Zou, Bi-Qun; Lu, Xing; Qin, Qi-Pin; Bai, Yu-Xia; Zhang, Ye; Wang, Meng; Liu, Yan-Cheng; Chen, Zhen-Feng; Liang, Hong
Abstract : Complex1 was more selective for MGC80-3 tumor cells versus normal cells (HL-7702). Importantly, 1 triggered MGC80-3 cells apoptosis via a mitochondrial dysfunction pathway. Abstract : Three novel 6-methyl-2-oxo-quinoline-3-carbaldehyde thiosemicarbazone (H-L ) transition metal complexes, [Cu(H-L )NO3 H2 O]·NO3 (1 ), [Zn(H-L )NO3 H2 O]·NO3 (2 ) and [CoL2 ] (3 ), were synthesized. In vitro antitumor screening revealed that complex1 exhibited better inhibitory activities than the commercial anticancer drug cisplatin against SK-OV-3 and MGC80-3 tumor cell lines, with IC50 values of 10.35 ± 1.26 μM and 10.17 ± 0.95 μM, respectively. All three complexes showed low cytotoxicity toward the normal human liver HL-7702 cells compared with cisplatin. Their binding properties to DNA were investigated by various methods. It was found that the complexes interacted with DNA mainly through intercalation, and their binding affinities ranked in the order of3 >1 >2 . Complex1 induced the highest apoptosis rate of MGC80-3 cells, and it caused cell arrest in the S phase according to flow cytometry. Further experiments confirmed that complex1 triggered MGC80-3 cells apoptosis via a mitochondrial dysfunction pathway.